Assessment of Maternal Infant and Young Child Nutrition (MIYCN) Knowledge and Practices Among Obstetricians and Pediatricians in Private Health Facilities in India. (14th June 2022) - Ghosh, Sebanti; DeMarco, Jessica; Jagtap, Shailesh; Sankhe, Lalit; Shastri, Vishal; Waghmare, Chhaya
Abstract: Objectives: i) To assess current MIYCN knowledge and practices among obstetricians and pediatricians in private facilities ii) To identify bottlenecks to adopting evidence- based MIYCN guidelines in private facilities Methods: The study used an observational cross-sectional design and mixed methods for an online self-administered survey with 360 pediatricians and 99 obstetricians (members of the Indian Academy of Pediatrics and Federation of Obstetric and Gynaecological Societies of India). The study included onsite interviews with 55 obstetricians and 59 pediatricians selected randomly during assessments in 114 private health facilities where they provided services across 3 purposefully selected cities in each of the 5 states (Uttar Pradesh, Bihar, Gujrat, Maharashtra and Karnataka). States were purposefully selected for high burden of undernutrition and high number of private practitioners. Results: Half of obstetricians knew the recommended dosage of iron supplementation during pregnancy, while 42% knew recommendations postpartum. Knowledge around weight gain during pregnancy and dietary requirements was limited. 75% of providers reported delayed initiation of breastfeeding in C-section deliveries. Over 90% of pediatricians knew about exclusive breastfeeding; but 40% of obstetricians and 11% of pediatricians had prescribed breastmilk substitutes. Only one third of pediatricians understood the importance of dietary diversity in complementary feeding. 70% of facilities had no maternal nutrition protocols. Roadblocks to optimal practices were lack of training and of evidence-based protocols, as well as non- recruitment of lactation counselors and dieticians. Half of the obstetricians and pediatricians reported ever being trained on MIYCN. Conclusions: Findings reveal a need to improve private obstetricians and pediatricians' knowledge on MIYCN and prioritize nutrition in medical associations' continuing education. Data support calls to action to institutionalize the integration of MIYCN into MNCH service protocols in private health facilities. Funding Sources: Bill & Melinda Gates Foundation through Alive & Thrive FHI Solutions.